Asian Lineage of Peste des Petits Ruminants Virus, Africa - Olivier Kwiatek; Yahia Hassan Ali; Intisar Kamil Saeed; Abdelmelik Ibrahim Khalafalla; Osama Ishag Mohamed; Ali Abu Obeida; Magdi Badawi Abdelrahman; Halima Mohamed Osman; Khalid Mohamed Taha; Zakia Abbas; Mehdi El Harrak; Youssef Lhor; et al. (Emerging Infectious Diseases, 2011)
Interest in peste des petits ruminants virus (PPRV) has been stimulated by recent changes in its host and geographic distribution. For this study, biological specimens were collected from camels, sheep, and goats clinically suspected of having PPRV infection in Sudan during 2000–2009 and from sheep soon after the first reported outbreaks in Morocco in 2008. Reverse transcription PCR analysis confirmed the wide distribution of PPRV throughout Sudan and spread of the virus in Morocco. Molecular typing of 32 samples positive for PPRV provided strong evidence of the introduction and broad spread of Asian lineage IV. This lineage was defined further by 2 subclusters; one consisted of camel and goat isolates and some of the sheep isolates, while the other contained only sheep isolates, a finding with suggests a genetic bias according to the host. This study provides evidence of the recent spread of PPRV lineage IV in Africa.